Royal figure holding a garland - Temples of India Project Team (Jio Institute, 2024)
A heavily bejewelled royal figure holding a garland is depicted on one of the pillars of the mahamandapa (pillared hall). While one might speculate that this figure could be representing the patron king, Vigraharaja IV, there's no conclusive evidence to support this theory.